Gerenciamento de projetos em uma empresa de bens de capital : uma comparação entre os procedimentos utilizados e o método da corrente crítica - Campanini, Luciano (2008)
The approach of this study relates to the method of project management originated of the Theory of Constraints called Critical Chain. Beyond of the bibliographical revision on research methodology, production systems, project management, simulation of systems, Theory of Constraints and Critical Chain, a case study was accomplished to compare two methods of project management in a company of Industrial Goods. This company works with projects under order and it uses the Critical Path Method (CPM) to make your projects management. To compare the two methods of project management, historical information on the current management method adopted by the company had been collected, and for the method of Critical Chain some simulations had been done. Through these simulations it was possible to compare the compliments of the finish dates and the lead-time of projects to each one of the management methods. The results indicate for a better execution of finish dates when the method of the Critical Chain is used in the project management.